FAKTOR–FAKTOR YANG MEMPENGARUHI MINAT AKSEPTOR VASEKTOMI DI KECAMATAN JEKAN RAYA KOTA PALANGKA RAYA - Marvianae, Melsa; Baringbing, Eva Prilelli; Ovany, Riska (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
The Family Planning Program is one of the government's efforts to suppress the rate of population growth in Indonesia. One of the contraceptive methods provided in this program is vasectomy, which is a long-term contraceptive method for men that is permanent. Although this method has a high level of effectiveness and a relatively low risk of side effects, the participation rate of men in the vasectomy program is still low, the majority of family planning participants are still dominated by women. The low interest of men to become vasectomy acceptors causes inequality in the role of birth control and can burden women physically and psychologically. This research is to find out the factors that affect the low interest of vasectomy acceptors in Jekan Raya District, Palangka Raya. Analytical survey with a cross sectional approach. The sampling technique was Accindental Sampling for 99 Respondents. The analysis carried out was univariate and bivariate analysis with Chi-Square statistical test. The research showed that there was an influence of age factors (?=0.000), education (?=0.000), knowledge (?=0.000), attitude (?= 0.004), wife's support (?=0.020), source of information (?= 0.000) on the husband's interest in becoming a vasectomy acceptor. There was an influence between factors of age, education, knowledge, attitude, wife's support and sources of information on the husband's low interest in becoming a vasectomy acceptor. The efforts to increase education and disseminate information that were right on target to increase men's participation in family planning programs through the vasectomy method. It is recommended to health workers and related parties to increase education about vasectomy to men of childbearing age. Clear, easy-to-understand, and targeted information was expected to increase men's understanding and interest in participating on family planning program in a balanced manner with women. ABSTRAKProgram Keluarga Berencana merupakan salah satu upaya pemerintah untuk menekan laju pertumbuhan penduduk di Indonesia. Salah satu metode kontrasepsi yang disediakan dalam program ini adalah vasektomi, yaitu metode kontrasepsi jangka panjang untuk pria yang bersifat permanen. Meskipun metode ini memiliki tingkat efektivitas yang tinggi dan risiko efek samping yang relatif rendah, tingkat partisipasi pria dalam program vasektomi masih rendah, mayoritas peserta KB masih didominasi oleh perempuan. Rendahnya minat pria untuk menjadi akseptor vasektomi menimbulkan ketimpangan peran dalam pengendalian kelahiran dan dapat membebani pihak perempuan secara fisik maupun psikologis. Penelitian ini untuk mengetahui faktor-faktor yang mempengaruhi rendahnya minat akseptor vasektomi di Kecamatan Jekan Raya Kota Palangka Raya. Survey analitik dengan pendekatan cross sectional. Teknik sampel adalah Accindental Sampling sebanyak 99 Responden. Analisis yang dilakukan adalah analisis univariat dan bivariat dengan uji statistik Chi-Square. Penelitian menunjukkan bahwa ada pengaruh faktor umur (?=0,000), pendidikan (?=0,000), pengetahuan (?=0,000), sikap (?= 0,004), dukungan istri (?=0,020), sumber informasi (?= 0,000) terhadap minat suami menjadi akseptor vasektomi. Ada pengaruh antara faktor umur, pendidikan, pengetahuan, sikap, dukungan istri dan sumber informasi terhadap rendahnya minat suami menjadi akseptor vasektomi. Upaya peningkatan edukasi dan penyebaran informasi yang tepat sasaran guna meningkatkan partisipasi pria dalam program KB melalui metode vasektomi. Disarankan kepada tenaga kesehatan dan pihak terkait untuk meningkatkan edukasi mengenai vasektomi kepada pria usia subur. Informasi yang jelas, mudah dipahami, dan tepat sasaran diharapkan dapat meningkatkan pemahaman serta minat pria dalam berpartisipasi pada program KB secara seimbang dengan perempuan.